MENGGALI POTENSI LOKAL DENGAN ANALISIS SWOT DI KELURAHAN TERUMBU KECAMATAN KASEMEN KOTA SERANG - Fatonah, Siti; Auliana, Sigit; Muhamadin, Ari; Saniyyasyah, Dinar Jauzaa; Nopfitasari, Nopfitasari (Gapenas Publisher, 2024)
This research aims to determine the local potential of the Terumbu sub-district through SWOT analysis. Local potential is an invaluable advantage of a region or region. SWOT analysis is an analysis based on logic that can maximize strengths and opportunities, but simultaneously minimize weaknesses and threats. The method in this research is descriptive qualitative. Data collection techniques used interview techniques with residents of the Terumbu sub-district. Observations were carried out directly in the Terumbu sub-district area. The results of the research show that the Terumbu sub-district has strengths that can be maximized in order to develop further, starting from owning large areas of rice fields, having gypang MSMEs, red bricks and having a strategic geographic location. Reefs also have weaknesses, namely, the clean and healthy lifestyle is very low, the habit of throwing rubbish carelessly, MCK (bathing, washing, toilet) is still in rivers/streams which are not clean. In terms of opportunities, it is still very possible for the Reef to be developed by providing counseling, assistance, training and education to increase the knowledge, skills and insight of the community. Apart from that, the threats to the Terumbu sub-district are diseases, chronic, infectious diseases, malnutrition, stunting and decreased intelligence. By suppressing existing weaknesses and threats through counseling, training, mentoring and education, the perception of the Terumbu sub-district changes from a bad perception to a good perception because it has succeeded in increasing local potential such as agricultural products, MSMEs and the lifestyle of its people for the better